Glycated hemoglobin: A powerful tool not used enough in primary care. Issue 3 (30th August 2017) - Salinas, Maria; López‐Garrigós, Maite; Flores, Emilio; Leiva‐Salinas, Carlos; ,
Abstract : Background: Glycated haemoglobin (HbA1c) is one of the most useful and relevant laboratory tests currently available. The aim of the actual research was to study the variability and appropriateness in the request of HbA1c in primary care, and differences between regions, to assess if there would be an opportunity to improve the request. Methods: A cross‐sectional study was conducted enrolling clinical Spanish laboratories. The number of HbA1c requested in 2014 by all general practitioners was reported by each participant. Test‐utilization rate was expressed as tests per 1000 inhabitants. The index of variability was calculated, as the top decile divided by the bottom decile. HbA1c per 1000 inhabitants was compared between the different regions. To investigate whether HbA1c was appropriately requested to manage patients with diabetes, the real request was compared to the theoretically ideal number, according to prevalence of known diabetes mellitus in Spain and guideline recommendations. Results: A total of 110 laboratories participated in the study, corresponding to a catchment area of 27 798 262 inhabitants (59.8% of the Spanish population) from 15 different autonomous communities (AACCs). 2 655 547 HbA1c were requested, a median of 93.9 (interquartile range (IQR): 33.4) per 1000 inhabitants. The variability index was 1.97. The HbA1c/1000 inhabitants was significantly different among the AACCs, ranging from 73.4 to 126.3. A total of 4 336 529 additional HbA1c would have been necessary to manage patients with diabetes according to guidelines, and 3 861 769 for diagnosis in asymptomatic patients. Conclusions: There was a high variability and significant differences between Spanish AACCs. Also a significant under‐request of HbA1c was observed in Primary Care in Spain.